Chlorophyll Meter’s Estimate of Weight-based Nitrogen Concentration in Rice Leaf is Influenced by Leaf Thickness - Li Jinwen; Yang Jingping; Li Dongsheng; Fei Pinpin; Guo Tiantai; Ge Changshui; Chen Wenyue (Plant Production Science, 2011)
The chlorophyll meter (SPAD) has been widely used to measure the leaf N concentration. Nevertheless, linear regression equations of SPAD readings on N concentration (based on dry weight, Nw) differ with plant age and genotype mainly due to differences in specific leaf weight (SLW), and there is a close relationship between SLW and leaf thickness. This implies that SPAD readings may be influenced by leaf thickness alone. The present paper is to testify whether SPAD readings on rice (Oryza sativa L.) are influenced by variation in leaf thickness in different plant ages or genotypes. In a paddy field trial with rice Bing 9363 and in a lysimeter trial with 9 genotypes of rice, leaf thickness was measured using a specially developed displacement sensor. Leaf N was estimated using SPAD-502 and directly determined by Dumas combustion method. At 3 growth stages in the field trial, the degree of linear fit between Nw and SPAD values was poor (R2=0.557), but it was improved (R2 =0.729) by introducing leaf thickness as an independent variable. In pooled data of the lysimeter trial, the predication of Nw was also improved by introducing leaf thickness as a secondary independent variable, the coefficients being increased from 0.0114 (not significant) to 0.513. However, if the leaf N concentration was expressed based on leaf area (Na), the leaf thickness did not influence the value estimated from the SPAD reading in both trials.